The Watsons go to Birmingham--1963 : [compact disc, unabridged] : a novel - Curtis, Christopher Paul (Listening Library, 1996)
The ordinary interactions and everyday routines of the Watsons, an African American family living in Flint, Michigan, are drastically changed after they go to visit Grandma in Alabama in the summer of 1963.